Water dispersed fluorescent organic aggregates for the picomolar detection of ClO4− in water, soil and blood serum and the attogram detection of ClO4− in the solid state by a contact mode method. Issue 31 (19th July 2016) - Kumar, Rahul; Sandhu, Sana; Singh, Prabhpreet; Kumar, Subodh
Abstract : An aggregation–disaggregation based molecular probe allows the detection of 10 pM ClO4 − in solution and 6 × 10 −18 g cm −2 ClO4 − in the solid state by a contact mode method with a selectivity of ∼10 000 over other inorganic anions. Abstract : Fluorescent organic aggregates (FOAs) ofCS-1 have been used for the fluorescence based selective estimation of ClO4 − ions.CS-1 undergoes self-aggregation to form FOAs ( ϕ = 0.35) with a diameter of 140 ± 50 nm in aqueous medium. Dynamic light scattering and field emission scanning electron microscopy studies reveal that FOAs ofCS-1 undergo further aggregation to form larger particles upon addition of ClO4 − (10 pM–1 nM concentration) but at higher concentrations of ClO4 − ions, these FOAs undergo dis-aggregation to give finally a molecularly dissolved complex ofCS-1 and ClO4 − . This ClO4 − induced aggregation–dis-aggregation process of FOAs ofCS-1 is associated with super-amplified fluorescence quenching following two domains of non-linear complexation with K sv values of 2.42 × 10 8 M −1 and 3.59 × 10 5 M −1 and variation in the lifetime measurements of FOAs ofCS-1 at different concentrations of ClO4 − . The lowest limit of detection is 10 pM in solution and 6 × 10 −18 g cm −2 in the solid state by a contact mode method with a selectivity of ∼10 000 over other inorganic anions and allows the quantitative measurement of ClO4 − ions using front surface steady state fluorescence of paper strips coated withCS-1 . FOAs ofCS-1 find applications in the determination of ClO4 − in tap water, soil and also blood serum. ProbeCS-2, which differs fromCS-1 in lacking three methyl groups on the m -phenylene spacer, shows poor sensitivity (LOD 1.6 μM) towards ClO4 − . DFT studies ofCS-1 andCS-2 and their complexes with ClO4 − reveal the effect of methyl substituents on their geometries.